FAKTOR-FAKTOR YANG MEMOTIVASI MINAT MAHASISWI DALAM BERWIRAUSAHA DI POLITEKNIK NEGERI BATAM - Irawati, Rusda; Hati, Shinta Wahyu (UNIVERSITAS NEGERI SURABAYA, 2014)
Man or women have a nature and characterisricof entrepreneurship. Womanhas the potential to do any productive activity that produces and help the economy of family and more broadly national economy. Batam State Polytechnic committed cultived and to create entrepreneurship culture. In each semester, there is 70 % female student who had chances and opportunities to be able to become an independent prospective young entrepreneurs in various business sectors. This research purpose to know, what factors that motivated female student to be a young entrepreneurs and can be that factors influence the desire of female students to entrepreneurship. Category of this research is explanatory research and The relation which will be reviewed by is the success of yourself ( x1 ), tolerance against the risk ( x2 ) and a desire to feel freedom in working ( x3 ) against a desire to become entrepreneurs ( y ). Population in this research is a student of Batam State Polytechnic. The sampling technique is purposive sampling. A questionnaire distributed to 100 female students from the Department of engineering and non-engineering. The results showed that success of the self and the variable tolerance of risk significant effect, while the freedom in work do not affect significantly the interest of entrepreneurship